2022
DOI: 10.3390/medicina58070930
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Radiographic Features and Clinical Relevancy of Accessory Canals of the Canalis Sinuosus in Cypriot Population: A Retrospective Cone-Beam Computed Tomography (CBCT) Study

Abstract: Background and Objectives: This retrospective study aims to evaluate the prevalence, radiographic features, and clinical relevancy of the accessory canals (AC) of the canalis sinuosus (CS) in patients referred for implant surgery. Materials and Methods: Cone-beam computed tomography (CBCT) images of the patients were collected and ACs were evaluated. Age, sex, bilateral distribution, localization, diameter, distance to the buccal cortical plate, distance to the crest of the alveolar ridge, terminal ending loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
3
6
1
Order By: Relevance
“…This result is consistent with that of another study, which reported a prevalence of 58.0% in males and 46.6% in females in a sample of 1000 patients [12]. It is noteworthy that the presence of AC was unrelated to age in the current study, which is consistent with the results of previous investigations [2,3,9,12,16,19,27].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result is consistent with that of another study, which reported a prevalence of 58.0% in males and 46.6% in females in a sample of 1000 patients [12]. It is noteworthy that the presence of AC was unrelated to age in the current study, which is consistent with the results of previous investigations [2,3,9,12,16,19,27].…”
Section: Discussionsupporting
confidence: 94%
“…The average distance between the nal position of AC and the peak of the alveolar ridge was 5.78 ± 2.25 mm. This outcome is in line with the ndings of two more studies [3,19], where the longest distance recorded was 15.72 mm, and the shortest distance recorded was 1.1 mm. In the assessment of the position relationship between AC and the maxillary anterior teeth, 845 among 870 ACs showed a horizontal relationship with the roots of the anterior teeth within the alveolar bone, whereas only 25 ACs were located above the roots.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No relationships regarding the prevalence or sidedness of CS and sex were found in the present study. This is consistent with studies conducted in Brazilian, Belgian, Turkish, German, Chinese, Australian, and Cypriot populations [ 1 , 3 , 5 , 7 , 11 , 17 , 18 , 29 ]. Age was also shown to have no effect on the presence or sidedness of CS, in keeping with studies of Brazilian, Turkish, Russian, and Chinese populations [ 1 , 6 , 7 , 12 , 13 , 17 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Ferlin et al .’s review of literature suggested CBCT scans to be the best modality for the evaluation of CS, where conventional radiographic techniques (periapical and panoramic radiographs) proved less effective [ 8 ]. Many studies investigating CS and its ACs have evaluated CBCT scans [ 1 , 2 , 5 7 , 11 13 , 17 19 , 25 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%